Comparison of the results of Teflon felt and Dacron strip usage in Stanford type A dissection - Demir, Deniz; Kahraman, Nail (The European Research Journal, 2019)
Objectives: In patients who undergo surgery for aortic dissection, the anastomotic leakage and the bleeding in these regions affect surgical success and mortality rate significantly. Various surgical materials are used for this purpose. We examined the results obtained from patients in whom Teflon felt strip or Dacron strip was used for creating a more secure anastomotic suture line.Methods: Twenty-eight patients who underwent surgery for ascending aortic dissection between 2013 and 2017 were examined retrospectively. Teflon felt strip or Dacron strip was used to create a more secure anastomotic suture line and to reduce bleeding in these patients. The patients were divided into the Teflon and Dacron groups according to the materials used. The amount of drainage, the amount of tissue adhesive used, the number of red blood cell (RBC) transfusions, and the morbidity and mortality rates were mainly compared between the two groups.Results: While Teflon felt strip was used in 13 (46%) patients, Dacron strip was used in 15 (53%) patients. The mean amount of drainage in the first 24 hours postoperatively was 596.15 ± 165.15 ml in the Teflon group and 546.67 ± 217.5 ml in the Dacron group. There was no statistically significant difference between the two groups in terms of mean amount of drainage (p = 0.509). Similarly, the mean number of RBC transfusions was 2.54 ± 0.51 units in the Teflon group and 2.33 ± 0.81 units in the Dacron group. There was no statistically significant difference between the two groups in terms of mean number of RBC transfusions (p = 0.416). Although the mean amount of tissue adhesive used was relatively higher in the Dacron group, there was no statistically significant difference between the two groups in terms of mean amount of tissue adhesive used (p = 0.761). The total mortality rate was 28% (8 patients). There was no statistically significant difference between the two groups in terms of mortality rate (p = 0.281). Conclusion: We concluded that the results obtained from the Teflon and Dacron groups were not significantly superior to each other. We think that Dacron strip may be used as an alternative to Teflon felt strip, which is used routinely in the surgical treatment of aortic dissection.